Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd006650.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation for the long term treatment of venous thromboembolism in patients with cancer

Abstract: For the long term treatment of VTE in patients with cancer, LMWH compared to VKA reduces venous thromboembolic events but not death. The decision for a patient with cancer and VTE to start long term LMWH versus oral anticoagulation should balance the benefits and downsides and integrate the patient's values and preferences for the important outcomes and alternative management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 48 publications
2
70
0
Order By: Relevance
“…[67], as well as two Cochrane reviews and metaanalyses on the treatment of VTE in patients with cancer [68,69], have been published. Overall, the conclusions of these studies are concordant with the recommendations proposed by our working group.…”
Section: Perspectivementioning
confidence: 99%
“…[67], as well as two Cochrane reviews and metaanalyses on the treatment of VTE in patients with cancer [68,69], have been published. Overall, the conclusions of these studies are concordant with the recommendations proposed by our working group.…”
Section: Perspectivementioning
confidence: 99%
“…[19][20][21][22] As observed in the current metaanalysis, the general finding was that for the long-term treatment of VTE in the overall population, LMWH compared to VKA provided no statistically significant benefit in the reduction of VTE recurrence. Our meta-analysis did not indicate that the dose of LMWH in patients without cancer had any influence on the recurrence of symptomatic VTE.…”
Section: Discussionmentioning
confidence: 52%
“…[19][20][21][22] Until studies that directly compare different LMWH doses for the treatment of VTE are performed, it is impossible to make definitive conclusions about their relative safety and efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…These recommendations are mainly based on the CLOT trial published in 2003 in which a therapeutic dose of the LMWH dalteparin was compared with warfarin in preventing recurrent thrombosis in patients with cancer [14]. Subsequent studies and a recently published systematic review of the current literature confirmed that LMWH compared with VKA significantly reduces the rate of venous thromboembolism, but not the mortality in cancer patients [15,16].…”
Section: Cancer-associated Venous Thromboembolismmentioning
confidence: 99%